Exploring performance development : |b perspective from colleagues of a not for profit organization - Utecht, Jennifer L. (University of Wisconsin--Stout, 2018)
The purpose of this study was to collect and analyze feedback from colleagues from Company XYZ regarding their previous experiences and opinions of performance management and employee development programs. A literature review was conducted to analyze performance management and employee development. Focus groups were conducted and themes were extracted from the feedback gathered at the focus group sessions.
Keywords: Career development; Performance; Employees